Creation of competitive advantage in improving the business performance of banking companies - Dina Patrisia; Muthia Roza Linda; Abror Abror (Jurnal Siasat Bisnis, 2022)
Purpose – This study aimed to examine the impact of innovation, intellectual capital and knowledge management, and competitive advantage on business performance. Design/methodology/approach – This study was conducted in Padang City, West Sumatra, Indonesia. The respondents are bank employees who have worked for more than five years and have structural positions in the company. The data has been collected using a survey with questionnaires. This study got 109 responses out of 135 questionnaires, so the response rate was 80.7%. It employed the Structural Equation Modeling (SEM) approach using Smart-PLS as the data analysis software. Findings – This study found that (1) innovation has a positive and significant effect on competitive advantage; (2) knowledge management has a negative but insignificant effect on competitive advantage; (3) intellectual capital has a positive and significant effect on competitive advantage; and (4) competitive advantage has a positive and significant effect on business performance. Surprisingly, it found that innovation significantly indirectly affects business performance through competitive advantage as a mediating variable. Intellectual capital has a significant indirect effect on business performance through competitive advantage as a mediating variable. Research limitations/implications – This study result can be more impactful considering several factors. First, this study is a cross-sectional study. Hence, it has a limitation in finding generalizations. Therefore, for further research, it could be expanded to a longitudinal study. Second, it is one country study. Future research might be extended to some countries with similar cultures, such as Southeast Asian Countries. Practical implications – This study has implications for the decision-makers. First, companies need to develop their intellectual capital through improving employee skills and applying information technology in business processes in order to maintain the company's competitive advantage so that it has an impact on improving the company's business performance. Second, the company is expected to be able to manage the knowledge owned by the company so that the knowledge it has can increase the creation of company innovation it provides a competitive advantage for the company. Originality/value –The contribution of this research is that the results of this study can be used as empirical evidence for banking companies of the importance of the role of IC, innovation, and KM in improving company performance by constantly creating the company's competitive advantage.